2019
DOI: 10.1111/1440-1681.13134
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical and biological characterization of PEGylated recombinant human endostatin

Abstract: Endostatin, a 20 kDa C-terminal fragment digested from collagen XVIII, is an endogenous angiogenesis inhibitor, which inhibits the migration and proliferation of endothelial cells, and potently suppresses tumour growth without inducing toxicity and acquired drug resistance. [1][2][3] Our studies proved that endostatin inhibits angiogenesis, lymphangiogenesis, and tumour progression, and also demonstrated that the molecular mechanism of endostatin is dependent on the internalization through the cell surface rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Strategies as the PEGylation of this molecule have been tested, with the aim of increasing its half-life and stability. In vitro studies have shown similar effectiveness as recombinant endostatin, but with a higher half-life [ 97 ] and showed no serious side effects on mice [ 98 ]. Additionally, an approach with liposome encapsulation of endostatin has shown favorable results in increasing its half-life [ 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…Strategies as the PEGylation of this molecule have been tested, with the aim of increasing its half-life and stability. In vitro studies have shown similar effectiveness as recombinant endostatin, but with a higher half-life [ 97 ] and showed no serious side effects on mice [ 98 ]. Additionally, an approach with liposome encapsulation of endostatin has shown favorable results in increasing its half-life [ 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cisplatin features an extremely strong peritoneal nodal penetration, and docetaxel and tegafur capsules can disrupt the microvascular meshwork, which, together with the inhibitory and modulatory effects of recombinant human endothelial inhibitor, effectively boosts the therapeutic effect. Prior studies have confirmed the significant clinical efficacy of bevacizumab, apatinib, and recombinant human endothelial inhibitor in combination with chemotherapy in the treatment of patients with a medium to advanced gastric cancer [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%